The Pre-Christian Religions of the North Project and its Archaeological Sources Database - Leszek Gardeła (Fasciculi Archaeologiae Historicae)
This paper presents the latest advancements of an ongoing interdisciplinary project entitled ‘Pre-Christian Religions of the North’ (PCRN) which aims at reevaluating previous understandings of pre-Christian beliefs in early medieval Northern Europe. The project will result in the production of a range of new academic handbooks supplemented by an online database comprising relevant textual and archaeological sources. The PCRN initiative gathers scholars from Europe, Australia and the USA. The core of the project comprises three strands 1. Sources, 2. Histories and Structures, 3. Research and Reception. The present paper discusses the latest work implemented within the framework of the ‘Sources’ strand and in particular the ongoing process of expanding its open access database of archaeological finds.